Alkaloids Alternatives in Synthesis, Modification and Application - Georgiev, Vasil; Pavlov, Atanas (IntechOpen, 2017)
The book Alkaloids - Alternatives in Synthesis, Modification, and Application collects several chapters written by distinguished scientists and recognized experts in their respective fields of research. The purpose of this book is to focus the attention of a broad range of students, researchers, and specialists on some innovative and highly perspective areas in alkaloid research. The book covers several topics, guiding the readers from the development of nonconventional biotechnologies for alternative production of valuable alkaloids, through the application of modern chemical methods of asymmetric synthesis for production of synthetic and semisynthetic alkaloid derivatives, medicinal application of alkaloids as anesthetics and pain-relief drugs, analytical techniques for alkaloid profiling and their application in chemotaxonomy, quality control and standardization of raw plant material, to the importance of the control and reduction of alkaloid contents during production of animal feedstuffs.